Advocacy for social and linguistic justice in TESOL
1 online resource
Keywords: "Recognizing the need for increased social justice in the fields of TESOL and English Language Teaching (ELT) globally, this volume presents a range of international case studies and empirical research to demonstrate how English language instruction can promote social and linguistic justice through advocacy-oriented pedagogies and curricula. Advocacy for Social and Linguistic Justice in TESOL adopts a critical, and evidence-based approach to identifying effective practice in ensuring inclusive and equitable learning and teaching. Chapters address emergent issues including heritage language and L1 attrition, teacher and learner identity, and linguistic colonialism, as well as wider issues such as global citizenship and human rights. Focus is placed on empowering both educators and learners as advocates of social justice and consideration is also given to how social responsibility can be supported through enhanced teacher preparation and professional development. Making a timely contribution at the intersection of advocacy, social justice, and English language teaching, this book will be key reading for postgraduate researchers, scholars, and academics in the fields of TESOL and ELT, as well as language education, applied linguistics, and the sociology of education more broadly. English language teachers and practitioners will also find this volume of interest"--